TEAM EMERGENCY SERVICE MODEL AS A HEALTH SERVICE MANAGEMENT STRATEGY IN WAKATOBI DISTRICT - Edi Hasan; Muhammad Nasir; Syamsir; Muhammad wajdi (International Journal of Multidisciplinary Research and Studies, 2022)
Public services are closely related to the government, one of which is the concept of development and management with Information and Communication Technology (ICT). The differentiation of the emergency service model is the emergency service team program. The purpose of this study was to determine the feasibility of implementing the emergency service team model in the health care setting. The method used is mixed methods research, which is a combination of quantitative methods that uses quantitative data analysis with SWOT analysis.